Data Science : An Introduction to Statistics and Machine Learning - Plaue, Matthias (Berlin: Springer, 2023)
This textbook provides an easy-to-understand introduction to the mathematical concepts and algorithms at the foundation of data science. It covers essential parts of data organization, descriptive and inferential statistics, probability theory, and machine learning. These topics are presented in a clear and mathematical sound way to help readers gain a deep and fundamental understanding. Numerous application examples based on real data are included. The book is well-suited for lecturers and students at technical universities, and offers a good introduction and overview for people who are new to the subject. Basic mathematical knowledge of calculus and linear algebra is required.
Keywords: Data Modeling; Machine Learning; Data Structures; Artificial Intelligence; Statistics; Probability; Knowledge & Systems; Information Theory